Memory Loss, Behavioral Changes, and Slurred Speech in a 49-Year-Old Man - Chugh, Chandril; Lee, John M.; Biller, Jose (Frontiers in Neurology, 2011)
A 49-year-old man presented with slurred speech, memory loss and behavioral changes. His clinical course was marked by decline in functional status and cognition. He had poorly controlled hypertension and hyperlipidemia. Neuroimaging was remarkable for multiple subcortical white matter lesions. We discuss the diagnostic and therapeutic approach of rapidly progressing cognitive decline in the given clinical setting.